دراسة توزع الأيونات الموجبة في الفرايت Co0.6Zn0.4Fe2O4 باستخدام ESR - الأعرج, بدر (Latakia University Journal -Basic Sciences Series, 2014)
تم في هذا العمل تسجيل إشارة التجاوب الإلكتروني السبيني ESR للفرايت Co0.6Zn0.4- عند درجة حرارة الغرفة. وحددت قيمة العزم المغناطيسي التجريبية بوساطة حساب الشدة التكاملية لهذه الإشارة وموضع القمة العظمى، وطبقت بعض العلاقات النظرية لتحديد قيم العزم المغناطيسي للفرايت المدروس. بعد ذلك،حدد توزع الأيونات الموجبة بين المواقع الرباعية والمواقع الثمانية في بنية الفرايت من قيم العزم المغناطيسي. علاوة على ذلك، حدد زمن حياة السوية الطاقية بالقيمة 1.38×10-10 sec. The ESR signal of the Co0.6Zn0.4Fe2O4 ferrite system was recorded at room temperature. The experimental magnetic moment value was estimated by means of integrated intensity of ESR signal and its maximum position.It has been used some theoretical relations were used to estimate the values of magnetic momentof the studied ferrite. The cation distributions between tetrahedral and octahedral sites were established from the values of magnetic moment.In addition, the lifetimeof energy level was determined.